Soil fertility and indigenous nutrient supply in irrigated rice domains of Asia - Dobermann, A.; Witt, C.; Abdulrachman, S.; Gines, H.C.; Nagarajan, R.; Son, T.T.; Tan, P.S.; Wang, G.H.; Chien, N.V.; Thoa, V. T. K.; Phung, C.V.; Stalin, P.; et al. (Wiley, 2003)
Knowledge‐intensive approaches have been proposed to manage the variability in indigenous nutrient supplies (IS) in irrigated rice (Oryza sativa L.) systems. On‐farm experiments were conducted at 155 locations in seven domains of Asia to quantify the variability of soil properties, grain yield, and nutrient uptake in N, P, and K omission plots (0‐N, 0‐P, and 0‐K, respectively). Except for pH, coefficients of variation of soil properties within a domain ranged from 17 to 43%. Similar ranges were measured for grain yield and plant nutrient uptake in nutrient omission plots, which served as crop‐based estimates of indigenous N, P, and K supply. Soil properties showed little association with plant nutrient uptake or grain yield in nutrient omission plots. Mean grain yields in nutrient omission plots increased in the order 0‐N (3.9 Mg ha−1) < 0‐K (5.1 Mg ha−1) ≤ 0‐P (5.2 Mg ha−1). Soils, climate, and crop management caused large variability of IS among irrigated rice domains, years, growing seasons, and fields within a domain. Grain yield and nutrient uptake in omission plots were mostly higher in high‐yielding than in low‐yielding climatic seasons. No changes in indigenous N supply occurred for periods of 4 to 6 yr in the same seasons. Grain yields in nutrient omission plots were strongly correlated with each other and also with the yield in the fertilized farmers' fields. Fertilizer recommendations should be fine‐tuned to spatial domains with relatively uniform agroecological characteristics, cropping practices, and socioeconomic conditions. Within such domains, season‐specific management of the IS variability can include field‐specific approaches.